Analisis Kualitas Udara Goa Seribu Banuarea - Istas Pratomo Manalu; Gerry Italiano Wowiling; Sari Muthia Silalahi; Marojahan Mula Sigiro; Eka Stephani Sinambela; Andriono Manalu (Prodi Teknik Mesin, 2023)
One of the technological advances that are starting to be applied in various fields is data transmission. Data transmission sends messages from one point to another to get or exchange information. To perform the data transmission, technology and tools are needed which can support the process. The technology that supports the data transmission system is the Wireless Sensor Network. The tool that supports the data transmission is LoRa. LoRa is a module that is able to support data transmission systems with a fairly long distance range. In this study, LoRa testing was carried out using several distances, namely 100 meters, 200 meters, 300 meters, 400 meters to get the RSSI and SNR values. The purpose of determining the RSSI and SNR is to find out how LoRa's performance is in sending data in the agricultural sector. The tests carried out are still in agricultural areas which are still in the category of many obstacles and a lot of noise. So that in the tests carried out LoRa can still be used to send data, it's just that the farther the transceiver is to the receiver, the more data will be lost. At a distance of 100 meters, 10 data are received. At a distance of 200 meters there are 9 data, at a distance of 300 meters there are 7 data and at a distance of 400 meters 3 data are received.